(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Organophosphorus is one of the most common causes of poisoning worldwide. Organophosphorus (OP) poisoning is a major public health problem in Nepal. This study was conducted to observe the epidemiological pattern and mortality in patients with OP poisoning admitted to provincial hospital Janakpurdham, Nepal. MATERIALS AND METHODS: It was a retrospective study. All the consecutive poisoning cases due to op compound admitted through emergency either in the ward or ICU of the provincial hospital from 15 May 2020 to 15 November 2020 included in the study. RESULTS: A total of 160 cases of poisoning were admitted through emergency either in the medical ward or ICU of the provincial hospital. Out Of these 81 (51.63 %) was OP poisoning. Among 81 cases 51.85 % were male.70.37 % of cases were from the young adult group i.e., 15 to 30 years. 38.37 % were housewives. Among all included cases 43.20 % had consumed Methyl parathion (Metacid) followed by Phorate 24.69 %. 55 % of total cases were from Dhanusha district followed by Mahottari and Sarlahi. The mortality rate was 14.81 % of total admitted cases, with an average of 5.7 days of hospital stay in the recovered case. CONCLUSIONS: OP poisoning is a major public health problem in province 2. It affects mostly the young age population. Housewives are at more risk of poisoning. The mortality in patients with OP poisoning is high even if antidotes are available. Considering the common occurrence and full curability of the condition early arrival to the hospital, timely monitoring, and prompt management may help to reduce mortality. With strict laws on the provision of pesticide availability, the poisoning incidence can be decreased and by proper development of infrastructure and ICU facility mortality can be decreased.